Variationsrechnung: 13.7. bis 19.7.1980 - Frehse, Jens; Jäger, Willi; Tomi, Friedrich (Tagungsbericht, 1980)
H. W. Alt, Heidelberg; I. Bakelman, Bonn; J. Bemelmanns, Bonn; R. Böhme, Bochum; M. Biroli, Milano; L. Caffarelli, Minneapolis; Dierkes, Bonn; G. Dziuk, Aachen; G. Eisen, Bonn; R. Finn, Stanford; J. Frehse, Bonn; A. Friedman, Evanston; C. Gerhardt, Heidelberg; M. Giaquinta, Firenze; G. Gilardi, Pavia; R. Gulliver, Minneapolis; E. Gonzales, Trento; E. Heinz, Göttingen; S. Hildebrandt, Bonn; E. Hölder, Mainz; P. A. Ivert, Bochum; W. Jäger, Heidelberg; J. Jost, Bonn; H. Kaul, Tübingen; B. Kawohl, Darmstadt; N. Killiman, Bayreuth; R. Landes, Bayreuth; H. Leinfelder, Bayreuth; S. Luckhaus, Heidelberg; M. Meier, Bonn; F. Morgan, Cambridge USA; J. C. C. Nitsche, Minneapolis; V. Oliker, Bonn; H. Pecher, Wuppertal; N. Quien, Saarbrücken; H. Ruchert, Saarbrücken; K. H. Schüffler, Düsseldorf; F. Schulz, Göttingen; E. Sperner, Bayreuth; G. Ströhmer, Aachen; E. Tausch, Bonn; F. Tomi, Saarbrücken; A. Torelli, Pavia; A. Tromba, Santa Cruz; W. v. Wahl, Bayreuth; H. C. Wente, Toledo; M. Wiegner, Bayreuth